2020
DOI: 10.1016/j.breast.2020.10.013
|View full text |Cite
|
Sign up to set email alerts
|

Individualized-thresholding Shear Wave Elastography combined with clinical factors improves specificity in discriminating breast masses

Abstract: Purpose To investigate the diagnostic role of new metrics, defined as individualized-thresholding of Shear Wave Elastography (SWE) parameters, in association with clinical factors (such as age, mammographic density, lesion size and depth) and the BI-RADS features in differentiating benign from malignant breast lesions. Methods Of 644 consecutive patients (median age, 55 years), prospectively referred for evaluation, 659 ultrasound detected breast lesions underwent SWE m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…Our study indicated that adding f mass to the statistical analysis improved the overall diagnostic performance. It was found in a previous study that SWS is underestimated in small lesions (Gu, et al 2020). This is partly owing to the shear wavelength being too large for accurate estimation of speed in relatively small masses.…”
Section: Discussionmentioning
confidence: 90%
“…Our study indicated that adding f mass to the statistical analysis improved the overall diagnostic performance. It was found in a previous study that SWS is underestimated in small lesions (Gu, et al 2020). This is partly owing to the shear wavelength being too large for accurate estimation of speed in relatively small masses.…”
Section: Discussionmentioning
confidence: 90%
“…Diverse techniques are used to study mechanical properties of tumors, including optical measurements, cantilevers, elastography (Fovargue et al, 2020), and pre-stressed surfaces (Staunton et al, 2016), but additional research on these and new techniques is still needed to understand the cell-microenvironment mechanical interaction. Recent literature describes the relationship between malignant lesions and anisotropy of breast cancer confirmed that malignant lesions are more anisotropic than benign (Sinkus et al, 2001;Skerl et al, 2016aSkerl et al, , 2016bGu et al, 2020;Böl et al, 2014;Soltaninezhad et al, 2020;Soleimani et al, 2020;Yang et al, 2020;Chen et al, 2018). In 2001, R. Sinkus et al observed a tendency of breast tumors to be anisotropic (Sinkus et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…However, not all tisues respond to these geometric configurations. On the other side, the growth of tumors is usually accompanied by processes of uncontrolled cell proliferation and migration in an anisotropic manner, proportionally to their malignancy (Gu et al, 2020). The asymmetry in these tissues is described by 21 elastic constraints, complex to be derived.…”
Section: Introductionmentioning
confidence: 99%
“…There are many advanced techniques to increase the biopsy result accuracy, such as stereotactic biopsy, 15–17 ultrasound elastography, 18,19 multiparametric magnetic resonance imaging/transrectal ultrasound (MRI/TRUS) fusion biopsy, 20 contrast‐enhanced MRI, 21 and high‐velocity pulse biopsy, 22 which are primarily complicated and expensive.…”
Section: Introductionmentioning
confidence: 99%
“…11 Also, a precise selection of vital neoplastic regions to take an accurate biopsy is crucial in large heteroge-nous masses, which could directly affect the pathological evaluations. 2,[12][13][14] There are many advanced techniques to increase the biopsy result accuracy, such as stereotactic biopsy, [15][16][17] ultrasound elastography, 18,19 multiparametric magnetic resonance imaging/transrectal ultrasound (MRI/TRUS) fusion biopsy, 20 contrast-enhanced MRI, 21 and highvelocity pulse biopsy, 22 which are primarily complicated and expensive.…”
Section: Introductionmentioning
confidence: 99%